Hubungan antara Kadar Feritin dengan Kreatinin Serum pada Pasien Thalassemia di RSUD Dr. Moewardi - Utami, Eko Dewi Ratna; Salimo, Harsono; Budiani, Dyah Ratna (Nexus Kedokteran Klinik, 2013)
Background : Patients with thalassemia that underwent routine blood transfusion are developing iron overload. In the state of excess iron, ferritin levels increase. When iron storage capacity has been depleted, free iron will cause tissue damage. One of that damaged organ is kidney. One of parameter used to know the function of kidney is GFR (Glomerular Filtration Rate). A simple way to estimate GFR is serum creatinine. Increased 1-2 mg/dL of creatinine serum showed decrease Â±50% of GFR. This research was aimed to determine the correlation between ferritin levels and serum creatinine of patients with thalassemia. Methods : A cross-sectional study which the subjects were 30 patients with thalassemia in the pediatric ward RSUD Dr. Moewardi who met the inclusion criteria. Ferritin levels and serum creatinine obtained from medical records or patient report book. Data normality was tested with Shapiro-Wilk normality test. Correlation between ferritin levels and serum creatinine were analyzed with non-parametric correlation test Spearman using Statistical Product and Service Solutions (SPSS) 20.0 for Windows. Results : Ferritin levels ranged from 1004.2 to 9600 ng/mL. Creatinine serum were 0.2 mg/dL; 0.3 mg/dL; 0.4 mg/dL; 0.5 mg/dL with almost equal distribution. Results of the analysis with non-parametric correlation test Spearman obtained R = 0.044 and p = 0.816. Conclusion : There was no correlation between ferritin levels and serum creatinine of patients with thalassemia. Keywords : thalassemia, ferritin, creatinine